Japanese psycholinguistics : a classified and annotated research bibliography - Kess, Joseph F. (Amsterdam studies in the theory and history of linguistic science. Library and information sources in linguistics ;, 1994)
This classified and annotated research bibliography is meant to serve as an introduction to the rich field of Japanese psycholinguistics, by providing an exhaustive inventory of what has been done in or about Japanese in a psycholinguistic sense. Thus, this volume captures the tradition of psycholinguistic research currently being pursued in Japan, its history and development over the past thirty years, and its current directions and research themes, as well as international research in modern psycholinguistics which targets the Japanese language as the focal point of empirical procedures or d.